Cu-Ti-BASED COPPER ALLOY SHEET, PRODUCING METHOD THEREOF, ENERGIZATION COMPONENT AND HEAT DISSIPATION COMPONENT
Patent Information
- Application Number
- JP2024010198
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-01-26
- Publication Date
- 2025-03-07
AI Technical Summary
【0022】 本発明に従うCu-Ti系銅合金板材は、厳しい曲げ加工を施したときに、曲げ加工部外周表面の理想的な平滑曲面のプロファイルに対し、乖離の小さい表面形態を得ることができる。これにより、例えば、狭ピッチ化された基板対基板(BtoB)コネクタにおける樹脂かぶりの問題が顕著に軽減されるといった効果が期待される。
Smart Images

Figure 2025031469000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cu-Ti-based copper alloy sheet having an improved surface morphology at a bent portion, a manufacturing method thereof, and a current-carrying part or a heat-dissipating part using the copper alloy sheet as a raw material. The Cu-Ti-based copper alloy is a copper alloy containing about 0.5 to 6% of Ti. [Background technology]
[0002] Cu-Ti copper alloys have a high level of strength and good stress relaxation resistance among various copper alloys, and are therefore useful for current-carrying spring parts such as connectors, relays, and switches, and heat dissipation parts for electronic devices. In recent years, as electronic devices have become smaller and thinner, there has been an increasing demand for thinner connectors and heat dissipation parts used in them, and it has become more important than ever for the copper alloy sheet material, which is the raw material, to have both strength and bending workability. Various studies have been conducted so far on methods to improve the strength and bending workability of Cu-Ti copper alloys.
[0003] Patent Document 1 discloses a technology for improving the strength and bending workability while maintaining stress relaxation resistance by optimizing the area ratio of crystal grains in which the GOS (Grain Orientation Spread) and Schmid factor determined by EBSD (Electron Backscatter Diffraction) satisfy predetermined ranges in a Cu-Ti based copper alloy. Patent Document 2 discloses a technique for improving the strength and bending workability of a Cu-Ti based copper alloy by obtaining a texture in which the area ratios of brass orientation, copper orientation, and S orientation are within a predetermined range. Patent Document 3 discloses a technique for obtaining an excellent balance between strength and ductility by controlling the morphology of the grain boundary reaction phase in a Cu-Ti based copper alloy.
[0004] Patent Document 4 discloses a technique for improving spring properties after bending by optimizing the conditions of solution treatment, cold rolling, and aging treatment in a Cu-Ti based copper alloy. Patent Document 5 discloses a technique for improving high-temperature fatigue resistance in a Cu-Ti-based copper alloy by optimizing the KAM value measured by EBSD. Patent Document 6 discloses a technique for simultaneously improving the strength, bending workability, and fatigue properties of a Cu-Ti-based copper alloy by optimizing the ratio of crystal grains whose KAM values measured by EBSD are within a predetermined range. Patent Document 7 discloses a technique for improving the strength and bending workability of a Cu-Ti-based copper alloy by optimizing the number density of second phase particles and the pole density of crystal grains within a range of 30° from the {111} plane.
[0005] Patent Document 8 describes a technique for improving properties such as strength and bending workability in a Cu-Ti-based copper alloy by carrying out a heat treatment that increases electrical conductivity after a final solution treatment, and then carrying out cold rolling and aging treatment. Patent Document 9 discloses a technique for improving fatigue resistance properties based on strict evaluation criteria in a Cu-Ti-based copper alloy by controlling the morphology of the grain boundary reaction phase through steps of performing a solution treatment, a preliminary heat treatment, and then performing cold rolling and aging treatment. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-66756 A [Patent Document 2] JP 2013-204140 A [Patent Document 3] JP 2015-140477 A [Patent Document 4] JP 2006-265611 A [Patent Document 5] JP 2014-84512 A [Patent Document 6] JP 2016-60958 A [Patent Document 7] JP 2012-12631 A [Patent Document 8] JP 2010-261066 A [Patent Document 9] JP 2015-175053 A Summary of the Invention [Problem to be solved by the invention]
[0007] When copper alloy sheet material is subjected to severe 90° bending at a BW where the ratio of bending radius R to sheet thickness t is about 1.0, microscopic wrinkles are formed on the outer peripheral surface of the bent part. As long as the wrinkles are not "cracks" that lead to cracks inside the thickness, they are usually considered to be no problem from the viewpoint of strength. For example, the bending workability evaluation stipulated in the technical standard JCBA T307 of the Japan Copper and Brass Association also adopts an evaluation method based on the appearance inspection of wrinkles. However, the surface morphology of the bent part cannot be correctly grasped by the size of the surface irregularities formed by the wrinkles (for example, the arithmetic mean roughness Ra based on the roughness curve). Since the material is stretched near the outer peripheral surface of the bent part, the actual surface profile deviates from the profile of an ideal smooth curved surface. When the deviation is large, the surface morphology can be considered to be a surface morphology in which the vicinity of the top of the outer peripheral surface of the bent part forms a "large concave part" that is generally depressed from the ideal smooth curved surface.
[0008] In current-carrying parts formed by integrating resin materials, such as board-to-board (BtoB) connectors, a phenomenon called "resin fogging" occurs during the resin molding process, in which resin gets into the recesses on the outer peripheral surface of the bent part, which can be problematic. Recently, electronic devices have become more sophisticated, and the need for miniaturization and narrower pitches in current-carrying parts and heat-dissipating parts such as connectors has increased accordingly. Thin-walled parts with narrow pitches, such as narrow-pitch connectors, are susceptible to the above-mentioned resin fogging, and it is difficult to solve the problem of resin fogging even with conventional Cu-Ti-based copper alloy materials intended to improve bending workability. To solve this problem, it is important not to simply reduce the surface roughness of the bent part (the depth of the recesses formed between each wrinkle), but to make the surface form have a small deviation from the profile of an ideal smooth curved surface.
[0009] The present invention aims to provide a Cu-Ti-based copper alloy sheet material having a property that, when subjected to severe bending, the deviation of the actual profile from the profile of an ideal smooth curved surface on the outer peripheral surface of the bent portion is kept small. [Means for solving the problem]
[0010] In order to achieve the above object, the present specification discloses the following invention. [1] In mass%, Ti (titanium): 1.00-5.50%, Ag (silver): 0-0.30%, Al (aluminum): 0-3.00%, B (boron): 0-0.30%, Be (beryllium): 0-0.15%, Co (cobalt): 0-1.00%, Cr (chromium): 0-1.00%, Fe (iron): 0-1.00%, Hf (hafnium): 0-1.00%, Mg (magnesium): 0-1.00%, Mn (manganese): 0-1.50%, Mo (molybdenum): 0-1.00%, Nb (niobium): 0-1.00%, Ni (nickel): 0-1.50%, P (phosphorus): 0-0.20%, S (sulfur): 0-0.20%, Si (silicon): 0-1.00%, Sn (tin): 0- The chemical composition of this steel is 1.50%, Ta (tantalum): 0-1.00%, V (vanadium): 0-1.00%, Zn (zinc): 0-2.00%, Zr (zirconium): 0-1.00%, and the sum of rare earth elements: 0-3.00%, with the sum of Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, and rare earth elements being 5.00% or less, with the balance being Cu (copper) and unavoidable impurities. When the measurement area on a cross section perpendicular to the rolling direction is performed using EBSD (electron backscatter diffraction) with a step size of 0.05 μm, the Area A copper alloy sheet material having an average crystal grain size of 8.00 μm or less by the fraction method, and an average GROD value of 7.0° or less, calculated by averaging the orientation differences between all measurement spots in the measurement region and the reference orientation of the crystal grain to which each measurement spot belongs, when the average orientation of measurement spots in the same crystal grain is taken as the reference orientation of the crystal grain.
[0011] [2] The copper alloy sheet material according to the above [1], wherein in the measurement by EBSD with a step size of 0.05 μm, a KAM value is 3.0° or less when a boundary having a crystal orientation difference of 5° or more is regarded as a crystal grain boundary. [3] The copper alloy sheet material according to the above [1] or [2], in which the ratio MBR / t of the minimum bending radius MBR at which cracks do not occur to the sheet thickness t in a 90°W bending test in BW in accordance with the Japan Copper and Brass Association technical standard JCBA T307:2007 is 1.7 or less. [4] The copper alloy sheet material according to any one of the above [1] to [3], having a tensile strength of 850 MPa or more in a direction parallel to the rolling direction. [5] The copper alloy sheet material according to any one of the above [1] to [4], having a sheet thickness of 0.02 to 0.50 mm.
[0012] [6] In a manufacturing process in which an intermediate product sheet material is subjected to a first solution treatment, an intermediate cold rolling, a final solution treatment, a finish cold rolling, an annealing before aging, and an aging treatment in the above order, The first solution treatment is carried out under the condition that the temperature is maintained in the range of 750 to 960°C, and then the cooling rate is maintained at 3 to 30°C / s from 750°C to 300°C, The intermediate cold rolling is performed under conditions where the total rolling ratio is 50 to 99%, The final solution treatment is performed by holding the material in the temperature range of 730 to 800°C, and then cooling it from 730°C to 300°C at an average cooling rate of 100°C / s or more. Finish cold rolling is performed under the conditions that the number of rolling passes with a reduction rate of 15% or more is 0 to 3, the average rolling load per unit width over all rolling passes is 620 kN / m or less, and the total rolling reduction rate is 3 to 55%, Pre-aging annealing is performed at a temperature range of 500 to 700°C for 25 to 600 seconds. The method for producing a copper alloy sheet material according to any one of the above [1] to [5], wherein the aging treatment is carried out under conditions of maintaining the temperature at 300 to 500°C.
[0013] [7] The method for producing a copper alloy sheet according to the above [6], wherein the intermediate product sheet is a sheet that has been subjected to cold rolling after hot rolling.
[0014] [8] An electrical conductive part using the copper alloy sheet material according to any one of [1] to [5] above as its material. [9] A heat dissipation component using the copper alloy sheet material according to any one of [1] to [5] above as its material.
[0015] In this specification, "sheet material" means a sheet-shaped metal material. A thin sheet-shaped metal material may also be called "foil", and such "foil" is also included in the "sheet material" referred to here. A long sheet-shaped metal material wound in a coil shape is also included in the "sheet material". In addition, in this specification, the thickness of the sheet-shaped metal material is called "sheet thickness". In this specification, the notation "n1~n2" indicating a numerical range means "n1 or more and n2 or less". Here, n1 and n2 are numerical values that satisfy n1 < n2.
[0016] The average crystal grain size, the average value of GROD (Grain Reference Orientation Deviation), and the KAM (Kernel Average Misorientation) value by EBSD (Electron Backscatter Diffraction) can be obtained as follows.
[0017] [Method for obtaining average crystal grain size] A cross section perpendicular to the rolling direction of the sheet material (hereinafter sometimes referred to as the "LD surface") is observed with a FE-SEM (field emission scanning electron microscope), and the crystal orientation is measured with an EBSD (electron backscatter diffraction) method at a step size (measurement pitch) of 0.05 μm for a rectangular measurement area of 48 μm in the sheet width direction and 36 μm in the sheet thickness direction, which is set within the range from the 1 / 4 position to the 3 / 4 position of the sheet thickness. If the sheet thickness is thin and a field of view of 36 μm in the sheet thickness direction cannot be secured, a rectangular measurement area of 48 μm in the sheet width direction and from the 1 / 4 position to the 3 / 4 position of the sheet thickness is measured. Using EBSD data analysis software, the boundaries with a crystal orientation difference of 5° or more are regarded as grain boundaries, and the grain size of all grains in the measurement area is obtained using a diameter chart, and the average grain size is calculated by the area fraction method. For grains whose part protrudes from the boundary of the measurement area, the area of the part existing in the measurement area is used as it is to calculate the average grain size. This operation is performed on five randomly selected non-overlapping measurement areas, and the arithmetic mean of the average grain size values obtained in the five fields is taken as the average grain size (μm). Note that twin boundaries ({111} / Σ3 coincidence boundary, {110} / Σ9 coincidence boundary) are ignored and are not considered as grain boundaries when calculating the average grain size. Here, the "1 / 4 thickness position" refers to a position in the thickness direction that is t / 4 (mm) away from one rolling surface, where t is the thickness (mm). Similarly, the "3 / 4 thickness position" refers to a position in the thickness direction that is 3t / 4 (mm) away from the rolling surface.
[0018] [How to calculate the average GROD value] Based on the above EBSD measurement data measured on the LD surface with a step size (measurement pitch) of 0.05 μm, EBSD data analysis software was used to regard boundaries with an orientation difference of 5° or more as grain boundaries (including twin boundaries ({111} / Σ3 coincidence grain boundary, {110} / Σ9 coincidence grain boundary)), and the average orientation of the measurement spots within the same grain was taken as the reference orientation of that grain. The value (°) of the orientation difference GROD (Grain Reference Orientation Deviation - Angle) between the reference orientation of the grain to which the spot belongs was calculated for all measurement spots in the measurement area, and the average of these was taken as the average GROD (°).
[0019] [How to calculate KAM value] Based on the above EBSD measurement data measured on the LD surface with a step size (measurement pitch) of 0.05 μm, EBSD data analysis software is used to calculate the KAM (Kernel Average Misorientation) value when boundaries (including twin boundaries) with an orientation difference of 5° or more are considered to be grain boundaries. This KAM value corresponds to the average value of all crystal orientation differences between adjacent spots (hereinafter referred to as "adjacent spot orientation differences") for electron beam irradiation spots arranged at a pitch of 0.05 μm, extracting only the measurement values of adjacent spot orientation differences that are less than 5°.
[0020] In the above 90° W bending test, BW stands for "Bad Way" and means that the bending axis is parallel to the rolling direction.
[0021] The reduction rate (%) in a certain rolling pass is determined by the following formula (1). Rolling reduction rate (%)=100×(t0-t1) / t0…(1) t0: Plate thickness before the rolling pass (mm) t1: Plate thickness at the end of the rolling pass (mm) The total rolling ratio (%) in a certain rolling process is determined by the following formula (2). Total rolling ratio (%) = 100 × (h0-h1) / h0…(2) h0: Plate thickness before the first pass of the rolling process (mm) h1: Plate thickness at the end of the final rolling pass of the rolling process (mm) Effect of the Invention
[0022] The Cu-Ti-based copper alloy sheet material according to the present invention can obtain a surface form that is small in deviation from the ideal smooth curved surface profile of the outer peripheral surface of the bent part when subjected to severe bending processing. This is expected to have an effect of significantly reducing the problem of resin fogging in, for example, narrow-pitch board-to-board (BtoB) connectors. [Brief description of the drawings]
[0023] [Figure 1] Photograph substituting a drawing illustrating the outer peripheral surface appearance of a bent piece of conventional material (Comparative Example No. 43). [Diagram 2] FIG. 2 illustrates a height profile measured for the surface of FIG. 1; [Diagram 3] An enlarged view of the apex of the profile in Figure 2. [Figure 4] 1 is a photograph in lieu of a drawing illustrating the outer peripheral surface appearance of a bent piece of the material of the present invention (Example No. 1). [Diagram 5] FIG. 5 illustrates a height profile measured for the surface of FIG. 4. [Figure 6] An enlarged view of the apex of the profile in Figure 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] [Chemical composition] Hereinafter, "%" regarding alloy components means "mass %" unless otherwise specified. Ti is an element that brings about the formation of a Ti modulation structure by spinodal decomposition and the formation of fine second phase particles by precipitation, and contributes to increasing the strength of the Cu-Ti-based copper alloy of the present invention. It also contributes to the improvement of stress relaxation resistance and the reduction of stress relaxation resistance. In order to fully exert these effects, a Ti content of 1.00% or more is ensured. From the viewpoint of precipitation strengthening, the Ti content is more preferably 1.50% or more, and even more preferably 2.50% or more. Excessive Ti content is a factor that reduces hot workability and cold workability, as well as a factor that reduces bending workability, so the Ti content is set to 5.50% or less. It may be controlled to 5.00% or less, 4.50% or less, or 4.00% or less.
[0025] Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements are optional elements. One or more of these can be contained as necessary. For example, Al is effective in suppressing the formation of coarse precipitates in Cu-Ti copper alloys, and is also effective in reducing the density (specific gravity) of copper alloys. Ni, Co, Fe, and Nb form intermetallic compounds with Ti and contribute to improving strength. In addition, the intermetallic compounds of these elements suppress the coarsening of crystal grains, making it possible to perform solution treatment at higher temperatures in the production of copper alloy sheet materials, which is advantageous in fully dissolving Ti. Ag and Sn have a solid solution strengthening effect and an effect of improving stress relaxation resistance. Zn is effective in improving solderability and strength, as well as improving castability. Mg has an effect of improving stress relaxation resistance and a desulfurization effect. Si can form compounds with Ti, which contributes to pinning during recrystallization in the production of copper alloy sheet material and can reduce the grain size. Cr and Zr are effective in dispersion strengthening and suppressing grain coarsening. Mn and V tend to form high melting point compounds with S, and B and P have the effect of refining the cast structure, so each can contribute to improving hot workability.
[0026] Rare earth elements (REM) are Sc (scandium), Y (yttrium), and the lanthanoid elements (excluding Pm (promethium)) in Group 3 of the periodic table. The inclusion of rare earth elements is effective in refining crystal grains and dispersing precipitates. Misch metal (a mixture of rare earth elements) may be used as a source of rare earth elements.
[0027] The contents of the above optional elements may be in the ranges of Ag: 0-0.30%, Al: 0-3.00%, B: 0-0.30%, Be: 0-0.15%, Co: 0-1.00%, Cr: 0-1.00%, Fe: 0-1.00%, Hf: 0-1.00%, Mg: 0-1.00%, Mn: 0-1.50%, Mo: 0-1.00%, Nb: 0-1.00%, Ni: 0-1.50%, P: 0-0.20%, S: 0-0.20%, Si: 0-1.00%, Sn: 0-1.50%, Ta: 0-1.00, V: 0-1.00%, Zn: 0-2.00%, Zr: 0-1.00%, and the sum of rare earth elements: 0-3.00%. The rare earth elements include, for example, one or more selected from La (lanthanum): 2.00% or less, Ce (cerium): 1.80% or less, Pr (praseodymium): 0.30% or less, Nd (neodymium): 0.80% or less, Sm (samarium): 2.50% or less, and Y (yttrium): 2.50% or less, with the total rare earth element content being 3.00% or less.
[0028] The contents of the above optional elements may be controlled within the following ranges: Ag: 0-0.20%, Al: 0-2.80%, B: 0-0.10%, Be: 0-0.08%, Co: 0-0.70%, Cr: 0-0.10%, Fe: 0-0.80%, Hf: 0-0.10%, Mg: 0-0.70%, Mn: 0-0.70%, Mo: 0-0.10%, Nb: 0-0.80%, Ni: 0-0.80%, P: 0-0.08%, S: 0-0.05%, Si: 0-0.20%, Sn: 0-1.20%, Ta: 0-0.10%, V: 0-0.10%, Zn: 0-0.50%, Zr: 0-0.20%, and rare earth elements total: 0-2.00%. In this case, a more preferable content range of rare earth elements that takes into further consideration economic efficiency and manufacturability can be, for example, a range including one or more selected from La: 0.50% or less, Ce: 1.00% or less, Pr: 0.15% or less, Nd: 0.40% or less, Sm: 1.80% or less, and Y: 1.00% or less, with the total content of rare earth elements being 1.80% or less.
[0029] The contents of the above optional elements may be controlled within the following ranges: Ag: 0-0.10%, Al: 0-2.60%, B: 0-0.03%, Be: 0-0.04%, Co: 0-0.35%, Cr: 0-0.02%, Fe: 0-0.60%, Hf: 0-0.01%, Mg: 0-0.40%, Mn: 0-0.40%, Mo: 0-0.01%, Nb: 0-0.50%, Ni: 0-0.30%, P: 0-0.03%, S: 0-0.015%, Si: 0-0.08%, Sn: 0-0.60%, Ta: 0-0.01%, V: 0-0.03%, Zn: 0-0.10%, Zr: 0-0.02%, and the sum of rare earth elements: 0-0.90%. In this case, a more preferable content range of rare earth elements that takes into further consideration economic efficiency and manufacturability can be, for example, a range including one or more selected from La: 0.30% or less, Ce: 0.50% or less, Pr: 0.05% or less, Nd: 0.20% or less, Sm: 0.80% or less, and Y: 0.60% or less, with the total content of rare earth elements being 0.80% or less.
[0030] From the viewpoint of the cost of the copper alloy, the total content of the above-mentioned optional elements Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements is preferably 5.00% or less, more preferably 3.00% or less, and even more preferably 2.00% or less, and may be controlled to 1.60% or less.
[0031] The inclusion of elements other than those mentioned above is permitted within a range that does not impair the object of the present invention (imparting a characteristic that suppresses the deviation between the ideal smooth curved surface profile of the outer peripheral surface of the bent part and the actual profile). Specifically, the total content of elements other than Ti, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, rare earth elements, and Cu (hereinafter, sometimes referred to as "unspecified elements") is preferably 0.50% or less, and may be controlled to 0.10% or less. The content of unspecified elements can be grasped, for example, by quantifying substantially all elements that can be contained in the copper alloy sheet material using the following analytical method.
[0032] (Example of quantitative determination method for alloying elements) O (oxygen) and N (nitrogen) are quantified using an oxygen / nitrogen / hydrogen analyzer (e.g., ONH-836, manufactured by LECO), H (hydrogen) is quantified using a hydrogen analyzer (e.g., EMGA-921, manufactured by Horiba, Ltd.), C (carbon) and S (sulfur) are quantified using a carbon-sulfur analyzer (e.g., CS844, manufactured by LECO), elements of the second to sixth periods (excluding C, N, O, group 17 elements, group 18 elements, Tc (technetium), Po (polonium), and Pm (promethium)) are quantified using ICP-MS (e.g., 7900, manufactured by Agilent), and F (fluorine), Cl (chlorine), and Br (bromine) are quantified using a combustion-ion chromatography apparatus (e.g., DIONEX ICS-1600, manufactured by Thermo Scientific).
[0033] Regarding the chemical composition of the copper alloy sheet material according to the present invention, it can be specified as "consisting of Ti, the above-mentioned optional elements (including cases where the total is 0% by mass), the balance Cu and unavoidable impurities", or it can be specified as "consisting of Ti, the above-mentioned optional elements (including cases where the total is 0% by mass), the above-mentioned unspecified elements (including cases where the total is 0%), the balance Cu".
[0034] [Average grain size] The copper alloy sheet material of the present invention is required to have an average grain size of 8.00 μm or less by the Area Fraction method when a boundary with a crystal orientation difference of 5° or more is considered as a grain boundary in an EBSD measurement of a measurement area provided on a cross section (LD surface) perpendicular to the rolling direction with a step size of 0.05 μm. If this requirement is not met, it becomes difficult to stably obtain an appropriate surface morphology in severe bending processing in BW. The above average grain size is more preferably 5.50 μm or less, and further preferably 4.00 μm or less, and can be adjusted to 2.00 μm or less. There is no particular lower limit for the average grain size, but since excessive refinement leads to an increase in the process load in the production of copper alloy sheet material, it is usually sufficient to control it to a range of 0.50 μm or more.
[0035] [Average GROD] The copper alloy sheet material of the present invention requires that the average GROD value is 7.0° or less when a boundary (including a twin boundary) with a crystal orientation difference of 5° or more is regarded as a grain boundary in the above EBSD measurement. The average GROD value corresponds to the average value calculated by calculating the orientation difference between all measurement spots in the measurement area and the reference orientation of the crystal grain to which each measurement spot belongs. Here, the average orientation of the measurement spots in the same crystal grain is adopted as the reference orientation of each crystal grain. The average GROD value is an index showing the magnitude of the residual stress accumulated inside each crystal grain as a whole sheet material. According to the research of the inventors, it was found that this average GROD value has a large effect on the shape of the outer peripheral surface of the bent part. In order to stably obtain an appropriate surface shape in severe bending processing with BW, it is extremely effective that the average GROD value is 7.0° or less. It is more preferable that it is 6.0° or less, and even more preferable that it is 3.7° or less. Although the lower limit of the average GROD value is not particularly set, excessive reduction in residual stress leads to an increase in the process load in the production of copper alloy sheet materials, so that it is usually sufficient to control it to a range of 1.0° or more.
[0036] [KAM value] The KAM value is an index that provides a clue to the extent to which local lattice strain (residual stress) exists in the entire sheet material. In order to obtain an appropriate surface morphology in severe bending processing in BW, in the above EBSD measurement in which the measurement step size is set to a minute size of 0.05 μm, the KAM value is preferably 3.0° or less when the boundary (including twin boundary) with a crystal orientation difference of 5° or more is regarded as a grain boundary. It is more preferable that it is 2.5° or less, and even more preferable that it is 2.0° or less. However, even if the KAM value meets this requirement, if the GROD average value is not controlled within the above-mentioned specified range, it is not possible to stably achieve an appropriate surface morphology in severe bending processing in BW. Although there is no particular lower limit for the KAM value, excessive reduction of the residual stress leads to an increase in the process load in the production of copper alloy sheet material, so it is usually sufficient to control it to a range of 0.3° or more.
[0037] [Maximum deviation from an ideal smooth curved surface on the outer periphery of the bent part] In the 90°W bending test with BW described later, it is desirable that the maximum deviation of the outer periphery of the bent part from the ideal smooth surface is 5.5 μm or less. It is also possible to obtain a sheet material with this maximum deviation of 4.0 μm or less, or even 3.0 μm or less. It is difficult to make this maximum deviation completely zero, and it is usually 0.1 μm or more. Details of how to determine the maximum deviation will be explained in the examples.
[0038] [MBR / t by 90°W bending test] In the copper alloy sheet of the present invention, the ratio MBR / t of the minimum bending radius MBR at which cracks do not occur to the sheet thickness t in a 90°W bending test in BW in accordance with the Japan Copper and Brass Association technical standard JCBA T307:2007 is preferably 1.7 or less, more preferably 1.3 or less. It is also possible to obtain a sheet with MBR / t of 0. Note that the MBR / t in this test is a conventional general index of bending workability evaluation that indicates how severe bending is required before cracks occur. In a Cu-Ti-based copper alloy sheet in which the chemical composition, average crystal grain size, and average GROD value are not controlled within the above-mentioned appropriate ranges, even if the bending workability based on MBR / t is good, it is difficult to stably realize a surface form with little deviation from an ideal smooth curved surface in severe bending in BW.
[0039] JCBA T307:2007 states that "This standard applies to the evaluation of bending workability of copper and copper alloy thin plate strips with a thickness of 0.1 mm or more and 0.8 mm or less." According to the inventors' study, it was confirmed that the bending workability can be evaluated by the W-bend test conforming to this standard even for Cu-Ti-based copper alloy plate materials with a thickness of less than 0.1 mm. Therefore, in the present invention, the W-bend test method in BW shown in JCBA T307:2007 is extended to the case of a plate thickness of less than 0.1 mm (for example, 0.02 mm or more and less than 0.1 mm) and is applied as it is. The width of the test piece may be, for example, 1 mm.
[0040] [Tensile strength] The tensile strength of the copper alloy sheet material of the present invention in the direction parallel to the rolling direction (LD) is preferably 850 MPa or more, more preferably 900 MPa or more. It is also possible to adjust the tensile strength in the rolling direction to a strength level of 1000 MPa or more. The upper limit of the tensile strength is not particularly limited, but it may be adjusted to, for example, a range of 1500 MPa or less, or may be adjusted to a range of 1300 MPa or less.
[0041] [conductivity] In applications of the copper alloy sheet material of the present invention, it is desirable to ensure electrical conductivity of 8% IACS or more (for example, 8% IACS or more and 25% IACS or less).
[0042] [Manufacturing method] The copper alloy sheet material described above can be manufactured, for example, by the following manufacturing process. Melting and casting → heating of the cast piece → hot processing → rough cold rolling → first solution treatment → intermediate cold rolling → final solution treatment → finish cold rolling → annealing before aging → aging treatment → (cold rolling after aging → low temperature annealing) The steps in parentheses above can be carried out as necessary. Although not described in the above steps, facing is carried out as necessary after hot working, and pickling, polishing, or further degreasing is carried out as necessary after each heat treatment. Each of the above steps will be explained below.
[0043] [Melting and Casting] A cast piece having the chemical composition specified in the present invention may be produced using a crucible furnace, etc. In order to prevent oxidation of easily oxidizable elements such as Ti, it is preferable to carry out the process in an inert gas atmosphere or in a vacuum melting furnace.
[0044] [Slab heating] The heating of the slab before the hot working can be carried out, for example, by holding it at 900 to 1000° C. for 0.5 to 5 hours.
[0045] [Hot processing, rough cold rolling] The method of hot working is not particularly limited. Usually, hot rolling or hot forging is adopted. In the case of hot rolling, the total hot rolling reduction ratio may be, for example, 60 to 99%. After the hot working is completed, it is preferable to rapidly cool the material by water cooling or the like. Then, cold rolling is performed. The cold rolling at this stage is called "rough cold rolling" in this specification. The rolling reduction ratio in the rough cold rolling can be, for example, 50 to 99%. In this way, an intermediate product sheet material to be subjected to the first solution treatment can be obtained.
[0046] [First solution treatment] The intermediate product sheet material is subjected to a first solution treatment. In this solution treatment, the strain introduced by the rough cold rolling is used as a driving force to recrystallize, and the coarse grain boundary reaction type precipitates and granular precipitates generated by casting and hot working are sufficiently dissolved. If the precipitates are not sufficiently dissolved at this stage, it becomes difficult to sufficiently generate fine precipitates that contribute to strength in the aging treatment process. The heating holding temperature of the first solution treatment is set in the temperature range of 750 to 960 ° C, more preferably in the temperature range of 780 to 880 ° C. If the heating holding temperature is higher than 960 ° C, the crystal grains may become too large. The holding time in the heating holding temperature range may be set, for example, in the range of 10 to 600 seconds. In the cooling process after heating and holding, it is important to control the cooling rate to a relatively slow rate rather than rapidly cooling the temperature range where precipitates are likely to be generated. Specifically, the cooling rate is maintained at 3 to 30 ° C / s from 750 ° C to 300 ° C. As a result, coarse precipitates are formed during the cooling process, but do not contribute to precipitation strengthening. The pinning effect of these coarse precipitates is exerted in each heating process described below, suppressing the growth of crystal grains and ultimately making the crystal grains finer. However, water cooling is not used in this process, since the cooling rate would normally exceed 100°C / s.
[0047] [Intermediate cold rolling] Cold rolling applied to material that has completed the first solution treatment is called intermediate cold rolling. The purpose of intermediate cold rolling is to reduce the plate thickness as well as to introduce strain. If strain is not introduced sufficiently, the recrystallization nucleation sites cannot be sufficiently secured in the subsequent final solution treatment, making it difficult to refine the crystal grains. In intermediate cold rolling, the total rolling reduction is 50% or more. It is more effective to set the total rolling reduction to 85% or more, and even more effective to set it to 90% or more. There is no particular upper limit on the total rolling reduction, but it is usually set to 99% or less depending on the capacity of the cold rolling mill.
[0048] [Final solution treatment] In the material that has been through the intermediate cold rolling, the precipitates have already been sufficiently dissolved, and strain has been introduced into the crystals of the matrix (metallic base). The sheet material in this structure is then subjected to a final solution treatment. In this final solution treatment, the strain introduced by the intermediate cold rolling is utilized to cause new recrystallization from many places, thereby refining the crystal grains. Since the main purpose is not to dissolve the precipitates, but to refine the crystal grains by recrystallization, the allowable upper limit of the heating temperature is lower than that of the first solution treatment. Specifically, the temperature is held in the range of 730 to 800°C. The holding time in the heating holding temperature range may be set within the range of 10 to 600 seconds, for example. The coarse precipitates that are generated during the cooling process of the first solution treatment are already present in sufficient quantities to exert the pinning effect. If many new precipitates are generated during the cooling process of this final solution treatment, this will have an adverse effect on the strength and bending workability. Therefore, in this final solution treatment, the cooling is performed at a fast cooling rate so that new precipitation is not generated as much as possible. Specifically, cooling is performed so that the average cooling rate from 730°C to 300°C is 100°C / s or more. For example, when a plate material coming out of a furnace is cooled by water to 300°C or less, this usually corresponds to cooling at an average cooling rate of 100°C / s or more.
[0049] [Finishing cold rolling] The cold rolling applied to the material after the final solution treatment is called "finish cold rolling". In the finish cold rolling, the plate thickness is reduced and the microscopic crystal grain size determined by the EBSD measurement described above is refined. If the "cold rolling after aging" described later is not performed, the plate thickness after this finish cold rolling will be the plate thickness of the final product plate material. In this finish cold rolling, it is important to reduce the plate thickness while taking care not to give too much strain to the crystals, and careful control is required. Specifically, the number of rolling passes with a reduction rate of 15% or more is between 0 and 3, the average rolling load per unit width is 620kN / m or less, and the total rolling reduction rate is 3 to 55%. The rolling load per unit width is the value obtained by dividing the rolling load (kN) by the plate width (m).
[0050] [Annealing before aging] In the above-mentioned finish cold rolling, the introduction of strain is controlled to reduce, but in order to refine the crystal grains, the introduction of strain to a certain extent is unavoidable. In this state, it is still insufficient to fully impart the properties that make the shape of the outer peripheral surface of the bent part closer to the profile of an ideal smooth curved surface. Therefore, annealing is performed before the aging treatment to further reduce the strain to the extent that recrystallization does not occur. This annealing is called "pre-aging annealing". In the pre-aging annealing, a condition of holding in the temperature range of 500 to 700 ° C for 25 to 600 seconds can be adopted.
[0051] [Aging process] Next, aging treatment is performed. The aging treatment can be performed under general conditions so that fine precipitates are sufficiently generated. Specifically, the aging temperature can be set in the temperature range of 300 to 500°C. The holding time in that temperature range may be adjusted, for example, in the range of 1 to 24 hours. While the main purpose of pre-aging annealing is to reduce distortion, the main purpose of this aging treatment is to generate fine precipitates. The temperature of the aging treatment may usually be set, for example, about 100 to 300°C lower than the temperature of pre-aging annealing.
[0052] [Cold rolling after aging] If further final thickness adjustment is required, light cold rolling can be performed after aging. This cold rolling is called "post-aging cold rolling". In post-aging cold rolling, the total reduction ratio is preferably in the range of 20% or less.
[0053] [Low temperature annealing] When cold rolling is performed after aging, it is necessary to finally perform low-temperature annealing to reduce distortion. For the low-temperature annealing, for example, conditions of holding at 350 to 500° C. for 10 to 600 seconds can be adopted.
[0054] [Electrical components, heat dissipation components] In this manner, a Cu-Ti-based copper alloy sheet material can be obtained that has a property of realizing a surface form with little deviation from the ideal smooth curved surface profile of the outer peripheral surface of the bent part when subjected to severe bending. The final sheet thickness can be, for example, in the range of 0.02 to 0.50 mm. The current-carrying parts and heat-dissipating parts formed by a process including bending using this sheet material have high reliability in terms of durability of the bent part. EXAMPLES
[0055] Copper alloys having the chemical compositions shown in Table 1 were melted and cast. The resulting slabs (thickness: 50 mm) were heated at 950°C for 1 hour, then hot rolled to the thicknesses shown in Table 2, and water-cooled. After hot rolling, the oxide layer on the surface was removed by mechanical polishing (face milling), and each hot-rolled material was cold rolled to the thicknesses shown in the "Rough cold rolling" column in Table 2 to obtain intermediate product sheets. In addition, the analysis samples taken from the cast slabs were subjected to elemental analysis by the method described in the above-mentioned "Example of a method for quantifying alloying elements". As a result, in all examples, the total content of elements other than Ti, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, rare earth elements, and Cu was 0.10% or less.
[0056] The intermediate product sheets were subjected to the first solution treatment, intermediate cold rolling, final solution treatment, finish cold rolling, pre-aging annealing, and aging treatment in the order shown in Tables 2, 3, and 4 to obtain test materials for various evaluations described below. However, in Tables 2, 3, and 4, a hyphen (-) indicates that the process was not performed. Nos. 14, 20, 45, 46, and 53 were subjected to post-aging cold rolling and low-temperature annealing under the conditions shown in Table 4 after the aging treatment. Nos. 44 and 46 were cold rolled under the conditions shown in Table 4 before the aging treatment. No. 55 was not allowed to proceed to the subsequent processes because cracks occurred in the material during hot rolling.
[0057] In the final solution treatment, the cooling rate was controlled by gas cooling, except for the cases indicated as water-cooled in Table 3. Aging treatment was performed in a nitrogen atmosphere using a batch-type heat treatment furnace. In the cases where low-temperature annealing was performed, the plate material after low-temperature annealing was used as the test material, and in the other cases, the plate material after aging treatment was used as the test material. The plate thickness of the test material is shown in the "Final plate thickness" column in Table 4. The following investigations were carried out for each test material.
[0058] (Average grain size) A cross section (LD surface) perpendicular to the rolling direction of a sample taken from a test material was processed with a cross-section polisher (IB-19530CP, manufactured by JEOL Ltd.) at an acceleration voltage of 4 kV to prepare a sample surface for EBSD (electron backscatter diffraction) measurement. The sample surface was observed with an FE-SEM (JSM-7200F, manufactured by JEOL Ltd.) at an acceleration voltage of 15 kV and a magnification of 2500 times, and crystal orientation data was collected by the EBSD method with a step size of 0.05 μm for a rectangular measurement area of 48 μm in the plate width direction × 36 μm in the plate thickness direction set within the range from the 1 / 4 position to the 3 / 4 position of the plate thickness using an EBSD device (Symmetry, manufactured by Oxford Instruments) installed in the FE-SEM. Based on the crystal orientation data measured for the measurement areas of five non-overlapping fields, the average crystal grain size was calculated by the Area Fraction method according to the above-mentioned "Method of calculating the average crystal grain size". The EBSD data analysis software used was OIM-Analysis 7.3.1 manufactured by TSL Solutions Co., Ltd. (the same applies to the calculation of the average GROD value and KAM value described below).
[0059] (Average GROD) Based on the crystal orientation data collected by the above EBSD method, the average GROD value was calculated according to the above-mentioned "Method of calculating the average GROD value".
[0060] (KAM value) Based on the crystal orientation data collected by the EBSD method, the KAM value was calculated according to the above-mentioned "How to calculate the KAM value".
[0061] (Maximum deviation from an ideal smooth curved surface on the outer periphery of the bent part) A test piece with a length of 30 mm and a width of 0.3 mm was cut out from the test piece so that the longitudinal direction of the test piece coincided with the rolling direction at the surface of the test piece, and a 90°W bending test was performed at BW where the ratio R / t of the bending radius R (mm) to the plate thickness t (mm) was 1.0 in accordance with the method of the Japan Copper and Brass Association technical standard JCBA T307:2007. The outer peripheral surface of the bent part formed in the test piece was observed with a laser microscope (Olympus Corporation, LEXT OLS4000), and the height profile of the outer peripheral surface of the bent part was measured when scanning in a direction perpendicular to the width direction of the test piece. A 50x objective lens was used for observation. The height direction of the profile was set to the direction corresponding to the moving direction of the jig during bending. A specific measurement method will be described with reference to Figs. 1 to 3.
[0062] Figure 1 shows an example of an external photograph of the bent outer peripheral surface of the conventional material, Comparative Example No. 43, as viewed in the direction corresponding to the direction of travel of the jig during bending. The horizontal direction of the photograph is the width direction of the test piece (i.e., the direction parallel to the bending axis), and the straight lines parallel to the vertical direction of the photograph are the profile measurement lines. FIG. 2 illustrates the height profile measured for the surface of FIG. 1. In the measured profile (solid line), irregular irregularities are numerous at a depth position of about 15 μm from the apex (highest point of height). Therefore, a polynomial approximation curve (quadratic function) was created using data from the measured profile curve in the range of 15 to 25 μm deep from the apex. At that time, data from the measurement position (horizontal axis in FIG. 2) was acquired in increments of 0.25 μm, and the polynomial approximation curve was created using the least squares method. The polynomial approximation curve thus obtained was regarded as the "ideal profile" and was regarded as the cross-sectional curve of the ideal smooth curved surface of the outer periphery of the bent part. The ideal profile is shown by a dashed line in FIG. 2. It can be seen that the actual bent outer periphery surface has a surface form in which the apex is depressed. Figure 3 shows an enlarged view of the apex of the profile in Figure 2. The maximum value (μm) of the height direction distance between the ideal profile (dashed line) and the measured profile (solid line) at the same scanning direction position (horizontal axis position in Figure 3) is defined as the "maximum deviation." In the example in this figure, the maximum deviation was 8.3 μm.
[0063] This maximum deviation measurement was performed on five randomly set measurement lines for one test piece, and the maximum of the five maximum deviation values was taken as the maximum deviation of that test piece. The maximum deviation of three test pieces was determined for n=3 tests, and the average of the maximum deviation measurements of the three test pieces was adopted as the maximum deviation performance value of the test material. The maximum deviation performance value for example No. 43, an example of which is shown in Figures 2 and 3, was determined to be 7.8 μm.
[0064] The maximum deviation was measured for the bending test pieces of each test material by the above method. Cu-Ti-based copper alloy sheet materials having a maximum deviation of 6.0 μm or less by this test method are evaluated as having a property in which the surface morphology of the bent part is significantly improved compared to conventional ones.
[0065] FIG. 4 shows an example of an external photograph of the bent outer peripheral surface of No. 1, an example of the present invention, viewed in a direction corresponding to the direction of travel of the jig during bending. The horizontal direction of the photograph is the width direction of the test piece (i.e., the direction parallel to the bending axis), and the straight line parallel to the vertical direction of the photograph is the profile measurement line. FIG. 5 shows an example of a height profile measured for the surface of FIG. 4. FIG. 6 shows an enlarged view of the apex of the profile of FIG. 5. The vertical axis of FIG. 6 is enlarged twice as much as that of FIG. 3. In this example, the maximum deviation was 1.8 μm. The maximum deviation performance value for the example of No. 1, an example of which is shown in FIG. 5 and FIG. 6, was determined to be 1.8 μm.
[0066] (MBR / t by 90°W bending test) Apart from the evaluation of the maximum deviation, the bending workability was evaluated as follows by a normal bending test. The ratio MBR / t of the minimum bending radius MBR at which cracks do not occur to the plate thickness t was obtained by a W-bending test at BW in accordance with the Japan Copper and Brass Association technical standard JCBA T307:2007. The test piece size was 30 mm in the direction perpendicular to the rolling on the surface of the test material, and 1.0 mm in the rolling direction (width of the test piece). The presence or absence of cracks on the surface of the bent part was judged according to JCBA T307:2007. For samples judged to have "large wrinkles" in the appearance observation of the surface of the bent part, a sample was prepared by cutting the deepest wrinkle part perpendicular to the bending axis direction, and the polished cross section was observed with an optical microscope to check whether cracks had occurred that progressed into the plate thickness. If no such cracks had occurred, it was judged to have "no cracks observed". Considering the use of the material of the present invention, if the MBR / t in this test is 1.70 or less, it is evaluated to have good bending workability.
[0067] (Tensile strength) Tensile test pieces (JIS No. 5) were taken from each test material in the direction parallel to the rolling direction, and tensile tests were performed according to JIS Z2241 with the number of tests (n = 3) to measure the tensile strength. The average value of n = 3 was used as the performance value of the test material.
[0068] (conductivity) The electrical conductivity of each test material was measured by the double bridge average cross-sectional area method in accordance with JIS H0505. The above results are shown in Table 5.
[0069] [Table 1]
[0070] [Table 2]
[0071] [Table 3]
[0072] [Table 4]
[0073] [Table 5]
[0074] The examples of the present invention, in which the chemical composition and the manufacturing conditions of the plate material were strictly controlled within the above-mentioned appropriate ranges, all exhibited a structure state in which the average crystal grain size and the average GROD value were within the ranges specified by the present invention, and had the property that the maximum deviation from an ideal smooth curved surface of the outer periphery of the bent part (hereinafter simply referred to as "maximum deviation") was 6.0 μm or less. In addition, these also had good bending workability in a normal evaluation method, and good strength and electrical conductivity.
[0075] In contrast, in the comparative example No. 41, the temperature of the first solution treatment was too high, resulting in a large grain size. In addition, the number of passes with a reduction of 15% or more in the finish cold rolling, the average rolling load per unit width, and the total rolling reduction were high, resulting in a high average GROD. As a result, the improvement in bending workability was insufficient, and the maximum deviation was large. For No. 42, the temperature of the final solution treatment was high, so the precipitates that had formed during the cooling process of the first solution treatment and had a pinning effect were dissolved, resulting in a very large grain size. When the grain size is very large, the average GROD value tends to be high. As a result, the improvement in bending workability was insufficient, and the maximum deviation was very large. For No. 43, since annealing before aging was not performed, the average GROD value was high and the maximum deviation was large. For No. 44, the temperature of the final solution treatment was too high, which resulted in a large grain size, and the average GROD value was high because cold rolling was performed before aging. As a result, the maximum deviation was large. No. 45 had a large grain size because the temperature of the final solution treatment was high and no finish cold rolling was performed. In addition, the average GROD value was high because the temperature of the pre-aging annealing was low. As a result, the maximum deviation was large. No. 46 did not undergo the first solution treatment, so there were insufficient precipitates that exerted a pinning effect, and the final solution treatment temperature was high, so the crystal grain size was large. Also, cold rolling before aging was performed, so the average GROD value was high. As a result, the improvement in bending workability was insufficient, and the maximum deviation was large. For No. 47, the final solution treatment was not performed, so the grain size was large and the maximum deviation was large. No. 48 had a high average GROD value because the total reduction ratio of the finish cold rolling was high. As a result, the improvement in bending workability was insufficient, and the maximum deviation was large. For No. 49, the temperature of the first solution treatment was high and the cooling rate was also fast, resulting in a large grain size. As a result, the maximum deviation was large. In No. 50, the final solution treatment temperature was low, so recrystallization was insufficient, resulting in a large grain size. In addition, the average rolling load per unit width between passes was large during finish cold rolling, so the accumulated strain was large and the average GROD was high. As a result, bending workability was very poor, and the material broke in the bending test to measure the maximum deviation. For No. 51, the annealing temperature before aging was low, so the average GROD value was high and the maximum deviation was large. For No. 52, the average rolling load per unit width between passes was large during finish cold rolling, which resulted in a large accumulated strain and a high average GROD value. As a result, the maximum deviation was large. No.53 did not undergo the first solution treatment, so there were insufficient precipitates that exerted a pinning effect, and the final solution treatment temperature was high, so the crystal grain size was large. In addition, because finish cold rolling and annealing before aging were not performed, the average GROD value could not be reduced. As a result, the maximum deviation was large. No.54 had a low Ti content, so there were not enough coarse precipitates to provide a pinning effect, and the grain size was quite large. As a result, the average GROD value was also high. As a result, the improvement in bending workability was insufficient, and the maximum deviation was large. In addition, the low Ti content resulted in a lack of fine precipitates, and the strength level was low. No. 55 had a high Ti content, which caused cracks in the material during hot rolling, and further processing was discontinued.
Claims
1. In mass%, Ti: 1.00 to 5.50%, Ag: 0 to 0.30%, Al: 0 to 3.00%, B: 0 to 0.30%, Be: 0 to 0.15%, Co: 0 to 1.00%, Cr: 0 to 1.00%, Fe: 0 to 1.00%, Hf: 0 to 1.00%, Mg: 0 to 1.00%. , Mn: 0-1.50%, Mo: 0-1.00%, Nb: 0-1.00%, Ni: 0-1.50%, P: 0-0.20%, S: 0 ~0.20%, Si: 0-1.00%, Sn: 0-1.50%, Ta: 0-1.00%, V: 0-1.00%, Zn: 0-2.00 %, Zr: 0-1.00%, the total of rare earth elements: 0-3.00%, the total of Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements: 5.00% or less, the balance being Cu and unavoidable impurities, and in a measurement area provided on a cross section perpendicular to the rolling direction by EBSD (electron backscatter diffraction) with a step size of 0.05 μm, when a boundary with a crystal orientation difference of 5° or more is regarded as a crystal grain boundary, A copper alloy sheet material having an average crystal grain size of 8.00 μm or less by the fractional method, and an average GROD value of 7.0° or less, calculated by averaging the orientation differences between all measurement spots in the measurement area and the reference orientation of the crystal grain to which each measurement spot belongs, when the average orientation of measurement spots within the same crystal grain is taken as the reference orientation of the crystal grain.
2. 2. The copper alloy sheet material according to claim 1, wherein, in the measurement by EBSD with a step size of 0.05 μm, a KAM value is 3.0° or less when a boundary having a crystal orientation difference of 5° or more is regarded as a grain boundary.
3. 2. The copper alloy sheet material according to claim 1, wherein a ratio MBR / t of a minimum bending radius MBR at which cracks do not occur to a sheet thickness t in a 90° W bending test at B.W. in accordance with Japan Copper and Brass Association technical standard JCBA T307:2007 is 1.7 or less.
4. The copper alloy sheet material according to claim 1, having a tensile strength in a direction parallel to the rolling direction of 850 MPa or more.
5. The copper alloy sheet material according to claim 1, having a sheet thickness of 0.02 to 0.50 mm.
6. In a manufacturing process including a first solution treatment, an intermediate cold rolling, a final solution treatment, a finish cold rolling, a pre-aging annealing, and an aging treatment in the above order on an intermediate product sheet material, The first solution treatment is performed under the condition that the temperature is maintained in the range of 750 to 960°C, and then the cooling rate is maintained at 3 to 30°C / s from 750°C to 300°C, The intermediate cold rolling is performed under conditions where the total rolling ratio is 50 to 99%, The final solution treatment is performed under the condition that the temperature is kept in the range of 730 to 800 ° C., and then the average cooling rate from 730 ° C. to 300 ° C. is 100 ° C. / s or more; The finish cold rolling is carried out under the conditions that the number of rolling passes with a reduction rate of 15% or more is 0 to 3, the average rolling load per unit width over all rolling passes is 620 kN / m or less, and the total rolling rate is 3 to 55%, Pre-aging annealing is performed under conditions of holding at a temperature range of 500 to 700 ° C for 25 to 600 seconds, The method for producing a copper alloy sheet according to claim 1, wherein the aging treatment is carried out under conditions of maintaining the temperature at 300 to 500°C.
7. The method for producing a copper alloy sheet according to claim 6, wherein the intermediate product sheet is a sheet that has been subjected to cold rolling after hot rolling.
8. An electric current-carrying part using the copper alloy sheet material according to any one of claims 1 to 5 as a material.
9. A heat dissipation part using the copper alloy sheet material according to any one of claims 1 to 5 as a material.
Citation Information
Patent Citations
Titanium copper and its production method
JP2006265611A
Method for manufacturing titanium-copper for electronic component
JP2010261066A
Titanium copper, wrought copper product, electronic component and connector
JP2012012631A
Titanium copper
JP2013204140A
High-strength titanium-copper
JP2014084512A